Penentuan Kadar Besi dan Kesadahan pada Sumber Air di Kelurahan Besusu Tengah Kecamatan Palu Timur - Abdurrahman Mujahida; Sitti Aminah (Media Eksakta, 2022)
This study aims to determine whether the analyzed clean water meets the quality standard requirements set by PERMENKES RI No. 492 of 2010. The parameters measured in this study were pH, odor, temperature, color (in-situ testing) as well as iron and hardness which were tested ex-situ using Atomic Absorption Spectrophotometry and Complexometric Titration. The results of this study are the springs on the S. Parman road for the parameters of pH, color, hardness, and iron, respectively 8.26 pH; colorless; 120 mg/L; and 0.129 mg/L, where the results met the requirements but for the odor (fishy) and temperature (36oC) parameters did not meet the quality standards. Meanwhile, the water sources in the Besusu Tengah Village, which existed before the earthquake in Palu City, had met the requirements set by the government